PENDAMPINGAN PENGELOLAAN, LEGALITAS DAN DIGITAL MARKETING BUMDes DAN UKM DESA BINAAN MANISLOR, KEC. JALAKSANA KAB. KUNINGAN - Lili Karmela Fitriani; Wachjuni Wachjuni; Munir Nur komarudin; Taopik Mulyana Kuntara; Indra Lesmana; Anidathi Layla (Yayasan Education and Social Center, 2022)
The potential of the village is something that must be utilized as well as possible to provide progress for the village both culturally and economically. For this purpose, the devotional team of the Faculty of Economics, Universitas Kuningan conducted a mentoring program to BUMDes and UKM Manislor Village, Kec. Jalaksana, Kab. Kuningan, West Java. The goal is that BUMDes can develop to advance villages and SMEs can improve living standards for the better. The mentoring activities are carried out in the form of BUMDes manager training, Product Quality Improvement Training for BUMDes and SMEs, and Business Strategy Building Training through Digital Marketing for BUMDes and SMEs. The delivery of materials and training practices in mentoring to BUMDes and SMEs managers is carried out in the multipurpose building of Manislor village. This activity resulted in 52 SMEs having NIB on the OSS page, having a village SMEs web